ANALISIS HUKUM ISLAM TERHADAP PEMBAGIAN HARTA BERSAMA DI PENGADILAN AGAMA KEDIRI (Studi Putusan Nomor : 0168/Pdt.G/2014/PA.Kdr) - Moh. Muchsin (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2016)
This study focuses three aspects about (1) basic considerations of decision of Islamic Court (PA) Kediri No. 0168 / Pdt.G / 2014 / PA.Kdr, (2) how the legal basic of that Decision, and (3) how the views of Islamic law. This qualitative research illustrated an object that was consistent with the fact that the division of joint property in the Religious Court (Pengadilan Agama) of Kediri. With descriptive analysis and based on the research above concluding as follows: (1) Based on the facts found that during the marriage, Plaintiff never provide for Defendant and the acquisition of joint property of debts and loans are repaid with Defendant salary (2) The legal basic in the Decision is al-Nisa ' : 58 to establish the mandate of the law fairly and the judges divide the property along with the distribution from a part in to two part (3) Divide the property along with the distribution of one part for the Plaintiff and two part for defendants was the right for the former because keeping the personal rights to protect their property or get a property with a fine is one of the maqasid al-syari'yah goals.Keywords: Islamic Law, Joint Treasure, Religious Court Decision Kediri